SPECIES DIVERSITY INVENTORY OF BATROCHOFAUNA IN THE LOWER CURRENT OF THE STYR RIVER - Klуmenko, Mykola; Biedunkova, Olha; Trotsіuk, Viktor (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
of the batrahofauna of the water biotope in the lower course of the Styr River are presented in the sections with different levels of anthropogenic load. Relative consistency of the species diversity of representatives of the batrahofauna was revealed against the background of a decrease in their total numbers under conditions of increased anthropogenic load. During the period of research, the species richness of the batrahofauna was somewhat higher in the autumn period, compared with the spring season. It is suggested that a decrease in the number of frogs is a response of animals to the stressful impact of urbanization and pollution of the water biotope, and the factor of seasonality is crucial in the form action of their species diversity.